Chemical safety of children's play paints: Focus on selected heavy metals - Rebelo, Andreia (2015)
Children's play paints are widely used as didactic products in preschool activities. Besides direct skin contact, a great risk of oral exposure exists during its normal and foreseeable use. Due to the ubiquitous nature of most metals, their presence as impurities in all products is recognized as unavoidable. However, the toxic potential of most of them requires that their levels are kept as low as possible. The present study aimed to assess the content of selected heavy metals (Pb, Cd, Cr, Co, Ni, Mn, Cu and Zn) in “artist paints” (n = 54) and “face paints” (n = 12) commonly used in preschool establishments and available at low cost stores. Determinations were carried out by GFAAS (for Pb, Cd, Co, Cr and Ni) and FAAS (for Mn, Cu and Zn). The levels obtained [mean ± SD (maximum)] were: 0.48 ± 0.44 (1.98) μg g− 1 for Pb; 0.04 ± 0.04 (0.30) μg g− 1 for Cd; 0.17 ± 0.20 (1.47) μg g− 1 for Co; 1.36 ± 2.18 (9.40) μg g− 1 for Cr; 0.63 ± 0.56 (3.10) μg g− 1 for Ni; 19.8 ± 88.2 (718) μg g− 1 for Mn; 108 ± 260 (1458) μg g− 1 for Cu; and 130 ± 564 (3478) μg g− 1 for Zn. A safety assessment considering the estimated potential exposure and health-based limits (tolerable daily intakes) was performed. Overall, the results showed no reasons for safety concerns regarding the studied elements.